Consumer attitudes in field of Hungarian red paprika - Bódi Barbara (Review on agriculture and rural development, 2013)
Informed decision is a key issue in consumer science that has influenced the food control regime in Europe. Ground red paprika has got some specialities that make it a unique food stuff for Hungarian consumers: an uniquely Hungarian product or Hungaricum, in other words. This also means that beyond measurable quality parameters paprika accounts for an ethical value for Hungarian consumers. Considering this, it is even more important to provide a clear definition of products on the shelves at buying situations. Indication of quality categories certainly represents a critical part of food labelling. In case of red paprika, as a spice, the Hungarian “Food Book”, Codex Alimentarius Hungaricus nominates four different quality categories. In our study we have conducted a throughout analysis of the level of consumer comprehension in regard of these categories. We found that there is a complete misunderstanding in this issue. Only two out of the four quality categories were identified by the consumers. We also recorded perplexity when we asked the respondents to organize the valid four categories in order according their quality level. As a summary, we have to conclude that conditions of informed decision making have not been met in regard of red paprika purchasing in case of most of the Hungarian consumers.